1991
DOI: 10.1128/jvi.65.9.4893-4901.1991
|View full text |Cite
|
Sign up to set email alerts
|

Several CD4 domains can play a role in human immunodeficiency virus infection in cells

Abstract: The human immunodeficiency virus (HIV) uses the human CD4 glycoprotein as a receptor for infection of susceptible cells. Cells expressing a series of mutated forms of the CD4 gene have shown a variability in their ability to support replication of three HIV type 1 (HIV-1) and three HIV-2 strains. Moreover, when different stages of virus production were examined by a variety of assays, a consistent delay was observed in all cell lines containing CD4 mutants compared with those with intact full-length CD4. Ceils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 24 publications
2
33
0
Order By: Relevance
“…Thus, a CD4-lowering drug could inhibit viral infection by not only blocking viral entry, but also making the virus more prone to elimination by the neutralizing action of antibodies. Furthermore, as several domains of CD4 play an important role in regulating HIV entry of cells [73], a specific down-modulator of the complete CD4 receptor may be considered as a more effective antiviral agent.…”
Section: Cada a Specific Down-modulator Of Cd4mentioning
confidence: 99%
“…Thus, a CD4-lowering drug could inhibit viral infection by not only blocking viral entry, but also making the virus more prone to elimination by the neutralizing action of antibodies. Furthermore, as several domains of CD4 play an important role in regulating HIV entry of cells [73], a specific down-modulator of the complete CD4 receptor may be considered as a more effective antiviral agent.…”
Section: Cada a Specific Down-modulator Of Cd4mentioning
confidence: 99%
“…Distance effects might influence membrane fusion during cell entry of other viruses. Transferring the HIV binding site nearer to the cell membrane resulted in loss of fusion (35); however, this study was designed to define the CD4 domains which play a role in HIV entry and not to study a distance effect. It was also recently observed that retroviruses expressing a foreign epitope on their envelope specifically bound a new surface receptor but that infection was blocked at a postbinding step (10).…”
Section: Vol 70 1996mentioning
confidence: 99%
“…The graph shows the mean fluorescence channels for duplicate determinations with standard errors. 41). The MAbs against D3D4 of rat CD4 can be placed in distinct functional groups as a result of our experiments.…”
Section: Discussionmentioning
confidence: 99%